2021
DOI: 10.11648/j.ajcbm.20210501.14
|View full text |Cite
|
Sign up to set email alerts
|

Improving Properties of Cinder Blended Materials for Construction of Low Volume Roads in Mbeya Region Tanzania

Abstract: The study to improve engineering properties of cinder blended materials was conducted in Mbeya region Tanzania.The low volume roads (LVRs) comprises of 75% of the whole road network and serves about 80% of population in Tanzania. The abundant materials in Mbeya region are cinders/scoria, pumices and volcanic soils which are originated from volcanic action. The samples from four source materials which are Ituha cinder, Ituha pozzolan, Mlimanyoka clay and Mbalizi gravel were collected for laboratory tests. Chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Te Ethiopian rift valley is known for its large coverage of volcanic materials such as pumice, scoria, and cinder [27]. Melese and Hamisi Chengula and Kilango Mnkeni [28,29] reported that scoria is abundantly found in volcano-prone areas of the Ethiopian rift. From an application point of view, scoria gravel is widely used for the improvement of weak subgrade materials and as a replacement material for the production of light weight concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Te Ethiopian rift valley is known for its large coverage of volcanic materials such as pumice, scoria, and cinder [27]. Melese and Hamisi Chengula and Kilango Mnkeni [28,29] reported that scoria is abundantly found in volcano-prone areas of the Ethiopian rift. From an application point of view, scoria gravel is widely used for the improvement of weak subgrade materials and as a replacement material for the production of light weight concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Portland cement is the common material used for mortar and concrete production. Production of Portland cements requires significant amount of energy for drying of materials, calcination process, production of clinkers and grinding to fine powders [10,14,20]. The process of producing cement in the factory emits CO 2 to the atmosphere and it is estimated that 1tone of cement produces 550kg of CO 2 to the atmosphere [13,21].…”
Section: Introductionmentioning
confidence: 99%
“…Geopolymer binders has excellent properties, such as high early strength development, fire resistance, fast hardening and high resistance on aggressive environments [2,8,14]. Geopolymer binders are produced by activating materials rich in alumino-silicate by alkali metals which are mainly calcium, sodium and potassium [4,6,19,20]. Regardless of the several advantages of geopolymer binders over industrial cements, the critical challenge is the formation of efflorescence products which generally affects its durability [1,8,9,18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations